As mudanças promovidas pelas mídias sociais no marketing de relacionamento : um estudo multi-caso - Barcelos, Arthur Mateus Ignatowski (2018)
This study aimed to identify the changes that social media has caused in the relationship marketing of fashion retailers, identifying elements - be it financial, strategic, procedure or customer satisfaction - that have undergone some change within the or